Feasibility and cost of a medical student proxy‐based mobile teledermatology consult service with Kisoro, Uganda, and Lake Atitlán, Guatemala. (29th December 2014) - Greisman, Laura; Nguyen, Tan M.; Mann, Ranon E.; Baganizi, Michael; Jacobson, Mark; Paccione, Gerald A.; Friedman, Adam J.; Lipoff, Jules B.
Abstract Background The expansion of mobile technology and coverage has unveiled new means for delivering medical care to isolated and resource‐poor communities. Teledermatology, or dermatology consultation from a distance using technology, is gaining greater acceptance among physicians and patients. Objectives To evaluate feasibility and cost of a smartphone‐based teledermatology consult service utilizing a designated medical student proxy to facilitate all consults on site, and to evaluate the service's effect upon diagnosis and management. Methods An IRB‐approved smartphone‐based teledermatology consult service was established to serve two rural communities in the developing world: Kisoro, Uganda, and Lake Atitlán, Guatemala. Fourth‐year medical students were recruited as proxies for each site, responding to consults by local doctors and transmitting photographs and clinical information via a smartphone application to a dermatology resident and attending in the USA over an encrypted website. At the Ugandan site, when indicated, the medical student performed skin biopsies under supervision, and rotating Montefiore residents transported specimens back to the USA. Results From October 2011 to August 2012, 93 cases were evaluated by the consult service (57 from Uganda and 36 from Guatemala). Initial diagnoses changed completely in 55.9% (52 of 93) of cases, and management changes were recommended in 89.2% (83 of 93) of cases. The estimated total cost of supplies and technology was 42.01 USD per consult and 64.24 USD per biopsy (including processing). Given fixed upfront costs, the cost per consult decreased with each additional case. Conclusion Smartphone‐based systems for teledermatology consultation using a medical student proxy are feasible for delivery of care in the developing world at relatively little cost. Optimization and sustainability of this system requires and deserves further investigation in larger studies.